2004
DOI: 10.1051/0004-6361:20047120
|View full text |Cite
|
Sign up to set email alerts
|

Brightness temperature and size of the quiet Sun at 34.5 MHz

Abstract: Abstract. We present observations of the quiet Sun made at 34.5 MHz during the solar minimum period June-July 1986 and May-June 1987 with the Gauribidanur radio telescope and a grating array. The brightness temperature of the quiet Sun varied from 1.0 × 10 5 K to 4.5 × 10 5 K and the East-West diameter from 39 to 66 arcmin during the above periods. Only a weak inverse correlation is found to exist between the brightness temperature and the diameter of the quiet Sun and it does not strongly support the scatteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 16 publications
2
15
0
1
Order By: Relevance
“…Such interferometers provide the opportunity to define the location of radio emission sources and their sizes at decameter wavelengths if they have sizes from some minutes to tens of minutes. Such sizes are close to those of the quiet Sun (Aubier, Leblanc, and Boischot, 1971;Kundu, Erickson, and Gergely, 1977;Erickson et al, 1977;Bhonsle, Sawant, and Degaonkar, 1979;Abranin and Bazelian, 1986;Thejappa and Kundu, 1992;Sastry, 1994;Subramanian, 2004;Ramesh et al, 2006;Brazhenko et al, 2012;Stanislavsky, Koval, and Konovalenko, 2013) and the sources of Type III bursts (Abranin et al, 1976;Chen and Shawhan, 1978;Bhonsle, Sawant, and Degaonkar, 1979;Abranin et al, 1980;Suzuki and Dulk, 1985;Melnik et al, 2017), Type II bursts (Chen and Shawhan, 1978;Bhonsle, Sawant, and Degaonkar, 1979;Nelson and Melrose, 1985), and Type IV bursts (Gergely and Kundu, 1974;Chen and Shawhan, 1978) in the decameter range. Previously the sizes of these bursts were measured only occasionally at some discrete frequencies, but now we have the opportunity to observe radio emission of different bursts in the whole frequency band from 8 to 33 MHz on a regular basis.…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…Such interferometers provide the opportunity to define the location of radio emission sources and their sizes at decameter wavelengths if they have sizes from some minutes to tens of minutes. Such sizes are close to those of the quiet Sun (Aubier, Leblanc, and Boischot, 1971;Kundu, Erickson, and Gergely, 1977;Erickson et al, 1977;Bhonsle, Sawant, and Degaonkar, 1979;Abranin and Bazelian, 1986;Thejappa and Kundu, 1992;Sastry, 1994;Subramanian, 2004;Ramesh et al, 2006;Brazhenko et al, 2012;Stanislavsky, Koval, and Konovalenko, 2013) and the sources of Type III bursts (Abranin et al, 1976;Chen and Shawhan, 1978;Bhonsle, Sawant, and Degaonkar, 1979;Abranin et al, 1980;Suzuki and Dulk, 1985;Melnik et al, 2017), Type II bursts (Chen and Shawhan, 1978;Bhonsle, Sawant, and Degaonkar, 1979;Nelson and Melrose, 1985), and Type IV bursts (Gergely and Kundu, 1974;Chen and Shawhan, 1978) in the decameter range. Previously the sizes of these bursts were measured only occasionally at some discrete frequencies, but now we have the opportunity to observe radio emission of different bursts in the whole frequency band from 8 to 33 MHz on a regular basis.…”
Section: Introductionsupporting
confidence: 54%
“…These sizes are close to those obtained by Kundu, Erickson, and Gergely (1977) in interferometric observations by the radio telescope at Clark Lake, although those observations were carried out in the years of minimum solar activity. At the same time heliograph measurements (Abranin and Bazelian, 1986;Stanislavsky, Koval, and Konovalenko, 2013) the sizes by the method in which the radio source is passing through the antenna beam as was reported by Aubier, Leblanc, and Boischot (1971), Sastry (1994), Subramanian (2004), and Ramesh et al (2006), gave probably larger sizes. A distinction of sizes can be connected with their dependences on the activity of the Sun.…”
Section: Observationsmentioning
confidence: 56%
“…The most comprehensive and detailed studies of solar continuum emission have been fulfilled in the centimetermillimeter range of wavelengths. A small number of measurements of the flux densities and spectra of the undisturbed Sun radio emission have been made in lowerfrequency range (Aubier, Leblanc & Boischot 1971;Erickson et al 1977;Sheridan 1978;Abranin & Bazelyan 1986;Thejappa & Kundu 1992;Lantos & Alissandrakis 1999;Ramesh 2000;Subramanian 2004;Thejappa & MacDowall 2008), especially at decameter wavelengths (10-30 MHz) because of technical and observational difficulties. To extract a contribution of the quiet Sun on background of a strong radio emission of sky (Galactic noise) in this frequency range, it is necessary to use giant radio telescopes (with total collecting area > 10 5 m 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, these studies have clearly demonstrated that to a large extent, the scattering is responsible for the unusual behavior of the quiet-Sun radio emission, even though very idealized spherical symmetric density models for the solar corona, and Gaussian spectrum for the electron density fluctuations with arbitrary values for the relative level of density fluctuations and spatial scales l were used in these studies. However, some authors (Sastry 1994;Subramanian 2004;Ramesh et al 2006) argue against this scenario because the higher -values required by the scattering to lower the brightness temperatures to the observed values may cause an abnormal increase in the sizes of the radio Sun.…”
Section: Introductionmentioning
confidence: 99%